INFLUENCE OF STRUCTURAL PARAMETERS OF LOW-CARBON STEEL ON ELECTRIC ARC BURNING - Vakulenko, I. O.; Plitchenko, S. O.; Murashova, N. G. (Science and Transport Progress, 2017)
Purpose. The article is aimed to evaluate the influence of structural parameters of low-carbon steel on arcing process. Methodology. The values of the micro- and substructure characteristics of the electrode wire metal were changed by varying the parameters of heat treatment and cold deformation by drawing. The degree of plastic deformation was obtained by drawing blanks from different initial diameter to final dimension of 1 mm. The thermal treatment was carried out in electric chamber furnace of the SNOL-1,6.2,5.1/11-IZ type. The temperature was measured by chromel-alumel thermocouple and the electromotive force was determined using the DC potentiometer. In order to obtain the substructure of different dispersion degree the steel (after quenching from temperatures and tempering at 650°C for 1 hour) was subjected to cold drawing to reduction 17 – 80%. To form structure with different ferrite grain size the steel after drawing was annealed at 680°C for 1 hour. The microstructure was examined under a light and electron transmission microscope UEMV-100K at the accelerating voltage 100 kV. The grain and subgrain sizes were evaluated using the methodologies of quantitative metallography. A welding converter of the PSG-500 type was used to study the arc welding process of direct and reverse polarities. Findings. The experimentally detected value of the welding current, which depends on the degree of deformation during wire drawing, under conditions of stable arc burning of direct polarity is about an order of magnitude lower than the calculated value. Similar difference was found for the arc of reverse polarity: the experimental value of the welding current is 5...6 times less than the calculated value. Dependence analysis shows that, regardless of the polarity of the welding arc, a good enough agreement between the calculated and experimental values of the welding current is limited to deformations of 60%. For deformation degrees of more than 60%, the differences are explained by qualitative changes in the dislocation cell structure. Originality. In the conditions of stable arcing of different polarity for the electrode of low-carbon steel, an extreme dependence of welding current on the degree of cold plastic deformation was observed. Practical value. Influence of ferrite grain size of electrode wire on the value of welding current is much greater than that from substructure presence.